Implementation of Special Autonomy Policy In The Health Sector In Wondama Bay Regency West Papua Province - Eduard Nunaki; Murtir Jeddawi; Djo Hermansyah; Hyroni Misrowa (Green Publisher Indonesia, 2023)
The degree of public health and health services has not shown results that are in line with the objectives of the special autonomy policy. The data shows that the infant mortality rate (IMR) is still high and the maternal mortality rate is still high. The aim of the research is to analyze and explain the implementation of the autonomy policy, especially in the health sector, the influencing factors and to formulate a new model regarding the implementation of the special autonomy policy in the health sector in Wondama Bay Regency, West Papua Province. This research uses implementation policy theory put forward by Grindle which consists of content policy and implementation context policy. The research approach used in this research is a qualitative approach with a descriptive research type. Data collection techniques were carried out by interviews, observation and documentation. Data analysis techniques used were data reduction and conclusion. The results of the study show that the implementation of the special autonomy policy in the health sector is not optimal, thus it needs to involve many components (authority, affairs, finance, resources, attitude of implementers, community participation and so on). The